2005
DOI: 10.1111/j.1540-8167.2005.50157.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Tone: Myths and Realities

Abstract: The possibility, heard during a conference session while I was a graduate student, of measuring vagal tone from heart rate changes during respiration, hooked me into heart rate variability research. Vagal tone seemed to be a sort of Holy Grail. Anything that promised to increase it would be life sustaining, and that claim would be testable in an objective way. Loss of vagal tone could serve as an early warning signal and catastrophe could be prevented. The truth has proved to be far more complex, but it is my … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…By contrast, in patients with abnormal sympathetic nervous activity, the length of the QT C may be related to an index of enhanced sympathetic nervous activity, like the circulating level of noradrenalin [5,11]. Heart rate variability primarily reflects the tonic vagal activity [50]. Several previous studies have confirmed the presence of autonomic neuropathy in patients with cirrhosis [7,12,13], and the present study confirms the reduced heart rate variability as evidenced by the substantial reduction of all values of indices of heart variability from the present study (Table 6) with a relation to central and arterial hypovolaemia (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…By contrast, in patients with abnormal sympathetic nervous activity, the length of the QT C may be related to an index of enhanced sympathetic nervous activity, like the circulating level of noradrenalin [5,11]. Heart rate variability primarily reflects the tonic vagal activity [50]. Several previous studies have confirmed the presence of autonomic neuropathy in patients with cirrhosis [7,12,13], and the present study confirms the reduced heart rate variability as evidenced by the substantial reduction of all values of indices of heart variability from the present study (Table 6) with a relation to central and arterial hypovolaemia (Fig.…”
Section: Discussionmentioning
confidence: 87%
“…The relationship between critical reflection skills and rationality required in the rest of the research process is something that requires further examination. Hunt (1997) and Stein (2000) are in agreement that we venture in murky grounds when we explore the domain between critical reflection and rationality. Some authors (Hunt, 1997;Imel, 1998;Stein, 2000) also believe that the journey to becoming critical reflective is one that ventures onto paths that neither educator or student may ever have been before.…”
Section: Discussionmentioning
confidence: 56%
“…I think that clear boundaries and environment setting are more important than 'teaching'. (Stein, 2000) also believes 'how to teach different levels of critical reflection 'is still in need of additional research'. Stein also suggests that the effectiveness of commonly employed methods to teach critical reflection like journal-keeping is unclear.…”
Section: Emergent Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, Mezirow construed "critical reflection" as "an analytical discussion but also a 'contextual awareness'; that is, an appreciation of historical, social and political perspectives and underpinning assumptions" (2004,185). Stein (2000) merged contextual reflection with "cultural forces" such as "race, gender, ethnicity, institutional policies, and personal expertise" (p. 3).…”
Section: Integrating Reflective Practice In a Bachelor Of Lawsmentioning
confidence: 99%